Planning Assistance Freeware for Surgical Management of the Multiple Ligament Knee Injury: From Historical to Modern Surgical Procedures - Guerot, Maxime; Boukebous, Baptiste; Chanteux, Lucas; Bouhali, Haroun; Rousseau, Marc-Antoine; Maillot, Cédric (The Journal of Knee Surgery, 2025)
Anatomical knowledge and identification of multiple ligament knee injuries have considerably evolved during the last decade. Consecutively, a trend for anatomical reconstruction of these injuries emerged. These procedures are challenging and require precise planning. Moreover, the planning itself is made difficult by the variety of techniques, whose descriptions are scattered throughout the literature. The objective is to reference and categorize the different ligament reconstruction techniques to provide free planning assistance software using a standardized graphic chart.The search for ligament reconstruction techniques on nine different databases produced 1,536 articles. After reviewing for relevance, the authors included the full papers of the remaining 306 articles. From the reference lists of the selected articles reviewed, 96 studies describing original techniques were retrieved. Techniques were extracted, drawn following the same graphics chart, and classified into conceptual categories.After selection, 10, 4, 28, 28, and 26 articles described anterior cruciate ligament, posterior cruciate ligament, posteromedial corner, posterolateral corner, and anterolateral corner procedures for reconstruction, respectively. Early techniques often used tenodesis while nowadays various grafts are fixed to isometric points or anatomic landmarks. An interactive tool was created. It allows the visualization of selected reconstructions on axial, frontal, and sagittal representations of the knee. Tunnel position, preferred transplant type, and fixation mode are represented. The freeware is available at: https://apps.medecine.u-paris.fr/multilig/.The techniques described for the reconstruction of an isolated ligament or corner cannot always be extrapolated for multiple ligament knee injuries treatment. Bone stock and tunnel convergence are two main concerns to consider during planning. Sometimes, it could be necessary to sacrifice a potentially biomechanically superior approach if simpler reconstructions provide equivalent knee kinematics. Surgical options are multiple and scattered throughout the literature. Our study provides an open-source and clinician-accessible research tool for multiple ligament injuries planification using a standardized graphic chart.
Keywords: multiligament; reconstruction; technique